Children's opportunities in Germany: An application using multidimensional measures - Charlotte Bartels; Maximilian Stockhausen (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2016)
Single parents and unmarried couples are increasingly replacing the traditional nuclear family. This paper investigates if the greater variety in living arrangements contributes to increased resource disparities among children in Germany. Children in single parent families are disadvantaged in at least three dimensions decisive for their later achievements: material standard of living, parental education, and parental childcare time. We compute multidimensional inequality and poverty indices using SOEP data from 1991-2012. We distinguish between parental and publicly provided childcare, which is an increasingly important in-kind benefit in Germany. We find that both multidimensional inequality and poverty declined as expanded public childcare strongly reduces resource disparities among children.
Keywords: D30; D63; I32; J12; J13; 330; multidimensional inequality; multidimensional poverty; inequality indices; demography